2020
DOI: 10.32479/ijeep.10618
|View full text |Cite
|
Sign up to set email alerts
|

Isomorphic Drivers of Institutional Pressure and Importance of Environmental Management System Implementation Towards the Adoption Propensity of Green Ict

Abstract: The rapid development of the Internet has amplified the use of information and communication technology (ICT). This has raised concerns regarding environmental sustainability in the ICT industry in relation to carbon emission, high electrical energy consumption, and vulnerable e-waste management practices. Therefore, this study investigates the relationship between the isomorphic drivers of institutional pressure such as coercive, normative, and mimetic pressures, and the importance of implementing the Environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, we found that mimetic pressure is intimately related to organizational behaviors (Xie et al., 2021). Mimetic pressure results from positive feedback from pioneers regarding the effectiveness of a practice, which influences other companies to replicate the same successful practice (Islam, 2020). Mimetic pressure could increase sustainable practices within companies (Ji, 2020), including energy efficiency practices (Bensouda and Benali, 2022c).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, we found that mimetic pressure is intimately related to organizational behaviors (Xie et al., 2021). Mimetic pressure results from positive feedback from pioneers regarding the effectiveness of a practice, which influences other companies to replicate the same successful practice (Islam, 2020). Mimetic pressure could increase sustainable practices within companies (Ji, 2020), including energy efficiency practices (Bensouda and Benali, 2022c).…”
Section: Introductionmentioning
confidence: 91%
“…However, there are also forward-looking companies which practice product stewardship. Such companies invest in the development of new environmental technologies (Islam, Muthaiyah, & Fie, 2020). Companies should not only focus on the present requirements.…”
Section: Vision Of Sustainability For Companiesmentioning
confidence: 99%
“…Many companies focus on pollution prevention. However, there are also forward-looking companies which practice product stewardship and invest in development of new environmental technologies (Islam, Muthaiyah, & Fie, 2020). Companies should always focus on sustainability forthefutureratherthanonlysatisfyingthepresentrequirements.Theyshouldnotbeshortsighted andshouldunderstandtheimplicationsofthevariouspoliciesonfuturegenerations.Atthesame time,goodenvironmentalvisionshouldbebackedwiththeskillsrequiredtoimplementthevision.…”
Section: Sustainability Vision For Companiesmentioning
confidence: 99%